A PWM controller of a full bridge single-phase synchronous inverter for micro-grid system - Rahman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Md Ralib @ Md Raghib, Aliza 'Aini (IOP Publishing, 2017)
Nowadays, microgrid system technology is becoming popular for small area power management systems. It is essential to be less harmonic-distortion and high efficiency of the inverter for microgrid applications. Pulse width modulation (PWM) controller is a conventional switching control technique which is suitable to use in the microgrid connected power inverter system. The control method and algorithm of this technique are challenging, and different approaches are required to avoid the complexity for a customized solution of the microgrid application. This paper proposes a comparative analysis of different controller and their operational methods. A PWM controller is used to reduce the ripple voltage noise while a continuous current mode provides a small output ripple which gives steady-state error as zero on fundamental and cutoff frequency. To reduce the ripple current, higher frequency harmonic distortion, switching loss and phase noise, LC low pass filter is used on either side of input and output terminals. The proposed inverter is designed by MATLAB 2016a simulation software. A balanced load resistance (RL = 20.5 Ω) of star configuration and a dual input DC voltage of ± 35V are considered. In this design, the circuit parameters, the fundamental frequency of 50 Hz, the PWM duty cycle of 95%, the cutoff frequency of the switching controller of 33 kHz are considered. The inverter in this paper exhibits THD of 0.44% and overall efficiency approximately of 98%. The proposed inverter is expected to be suitable for microgrid applications.